Discourse Competences: A Case of English Foreign Language Students in Graduate Program - Gani, Citra Amiliani Abdul (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This study concerns with discourse competence in conversation. The aim of this study is to examine the speakers dominance, the most strategy used when the problems of communication arise, and the speakers discourse competence. The subject of this research is students of graduate program. The conversation involvedthree participants (speakers) of English students of educational program. The transcripts of conversationwere divided into turns, moves and clauses, and discourse competence was analyzed further based on the content specification of Celce Murcia (1995). Eventually, interpretation on the result of analysis was conducted. The findings of the study show that three speakers are dominant in the conversation. There is no incidental participant in the conversation due to they speak purposively. Additionally, the result concluded that the most frequently strategy that is used in thisconversation is stallingor time gaining. It indicates that the speakers have more problems of hesitation within the conversation. Therefore, this claims that the speakers are not fluent in speaking English. Though the conversation that is produced by the speakers is not well formed, the conversation has involved cohesion and coherence aspects. Therefore, it can be inferred that the speakers discourse competence is good since they produce utterances cohesively. According to the findings, it is suggested to the EFL students to produce more English in their daily activities to decrease the communication problems and increase their speaking competences. Besides, the lecturer also guide and stimulate studentscreatively to speak more English during EFL learning.